IDENTIFIKASI PENYAKIT YANG DISEBABKAN OLEH JAMUR DAN INTENSITAS SERANGANNYA PADA TANAMAN BUAH NAGA MERAH (Hylocereus polyrhizus) di KABUPATEN SIAK SRI INDRAPURA - Faidah, Fikriatul; Puspita, Fifi; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Red dragon fruit (Hylocereus polyrhizus) is a plant cultivated in Riau Province especially Siak district such as Tualang and Bunga Raya. However, productivity of dragon fruit is still low because attacks of diseases infection. The aim of the research is determine the diseases, the cause of the diseases and their intensity caused by fungi on the red dragon fruit plants. Based on the observation, the diseases that infected the dragon fruit plants are anthracnose disease caused by Colletotrichum sp., stem rot diseases by Sclerotium sp., and fusarium wilt by Fusarium sp., and orange spot diseases on fruit by Alternaria sp. The intensity of the disease attacks the dragon fruit in Bunga Raya higher  than in Tualang, i.e : 50% of anthracnose disease, 60% stem of rot disease, 30% of layu fusarium, 17,5% of orange spots on the fruit. While the intensity of the diseases in Tualang are 57.5% of anthracnose, 50% of stem rot diseases, 30% of fusarium wilt, and 15% orange spots on the fruit. Keywords : red dragon fruit plants, fungal disease, disease intensity